AppHolmes: Detecting and Characterizing App Collusion among Third-Party Android Markets - Xu, Mengwei; Ma, Yun; Liu, Xuanzhe; Lin, Felix Xiaozhu; Liu, Yunxin (WWW 2017, 2017)
164 papers have been accepted from the nearly 1000 papers submitted in the 11 Technical Tracks for WWW2017. They have been grouped into 40 sessions in 23 topic areas to be presented over three days, during Wednesday, Thursday and Friday. The accepted papers are listed below in their sessions ordered by day.